Formulation and characterization of dermal patch containing mangosteen (Garcinia mangostana L.) peel extract using ethyl cellulose and polyvinylpyrrolidone polymers - Ni Luh Dewi Aryani; Rismawati; Marisca Evalina Gondokesumo (Universitas Ahmad Dahlan, 2025)
Mangosteen peel extract (Garcinia mangostana L.) shows strong potential in treating diabetic ulcers. Topical applications via dermal patches enable direct delivery of active compounds while protecting wounds from contaminants, preventing bacterial invasion, and maintaining moisture factors essential for promoting effective wound healing in diabetic patients. The dermal patches of mangosteen peel extract were developed using a combination of EC and PVP K-30 polymers. Previously, the mangosteen peels were extracted utilizing the ultrasound-assisted extraction method. Subsequently, the dermal patches were prepared utilizing solvent casting techniques, employing a combination of ethyl cellulose and polyvinyl pyrrolidone in ratios of 1:3 (F1), 1:2 (F2), and 1:1 (F3). The dermal patches were assessed for their physicochemical properties, including organoleptic characteristics, thickness, weight uniformity, folding endurance, moisture uptake, moisture loss, and pH values. The content of alpha-mangostin was analyzed using UV spectrophotometry, while the interactions between the active ingredient and excipients were examined through Fourier Transform Infrared Spectroscopy. The crystallinity profiles were analyzed using an X-ray diffractometer. Surface morphologies were assessed using scanning electron microscopy. The dermal patches were thin, light yellow, smelled of menthol, uniform in size, and exhibited good folding endurance (>300 folds). The moisture uptake and moisture loss were minimal. The pH values ranged from 6.99 to 7.24. The total xanthone concentrations in patches F1, F2, and F3 were 95.26% ± 0.47, 71.42% ± 1.99, and 78.54% ± 0.47, respectively. It showed no chemical interaction between active ingredients and excipients and had amorphous forms. The surface morphologies displayed smoothness for F1, whereas F2 and F3 exhibited solid spots. It was concluded that formulation F1, which contained ethyl cellulose and polyvinyl pyrrolidone in a 1:3 ratio, was the optimal formulation.